2018
DOI: 10.1136/bmj.k4878
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the primary care access challenge in South Asia

Abstract: Increased public financing for primary care and medical education as well as regulation of private services are vital to tackle the primary care crisis in South Asia, argue Amit Sengupta and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Previous studies found that awareness about high blood pressure and use of antihypertensive medication is low in this region [24, 25, 32]. Also, the health systems are not well-prepared to manage the large burden of NDCs [33, 34]. Therefore, the policy makers should focus mainly on reduction of BMI at population level as one of the most important primary prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that awareness about high blood pressure and use of antihypertensive medication is low in this region [24, 25, 32]. Also, the health systems are not well-prepared to manage the large burden of NDCs [33, 34]. Therefore, the policy makers should focus mainly on reduction of BMI at population level as one of the most important primary prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…22,23,30 Also, the health systems are not well-prepared to manage the large burden of NDCs. 31,32 Therefore, the policy makers should focus mainly on reduction of BMI at population level as one of the most important primary prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The health system especially at the primary level in the region has inadequate public investment with scarce health care workforce and excessive out of pocket expenditure. 7 Over the past decade, the health system has shifted more towards medical-centric based care on the insurance mode for service provision from private sector. 8 The ignorance to public health is a major cause for high burden of morbidity and mortality, especially due to communicable diseases.…”
Section: Introductionmentioning
confidence: 99%